2022
DOI: 10.29207/resti.v6i3.4049
|View full text |Cite
|
Sign up to set email alerts
|

The Formula Study in Determining the Best Number of Neurons in Neural Network Backpropagation Architecture with Three Hidden Layers

Abstract: The researchers conducted data simulation experiments, but they did so unstructured in determining the number of neurons in the hidden layer in the Artificial Neural Network Back-Propagation architecture. The researchers also used a general architecture consisting of one hidden layer. Researchers are still producing minimal research that discusses how to determine the number of neurons when using hidden layers. This article examines the results of experiments by conducting training and testing data using seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The number of neurons in the input layer, hidden layer, and output layer was 36-73-37-19-1. This architecture is in accordance with the research results of Syaharuddin et al [53] who carried out training-testing on rainfall and temperature data from Lombok International Airport station. Furthermore, Syaharuddin et al [44,54] also tested several parameters of the backpropagation architecture with three hidden layers.…”
Section: Research Proceduressupporting
confidence: 87%
“…The number of neurons in the input layer, hidden layer, and output layer was 36-73-37-19-1. This architecture is in accordance with the research results of Syaharuddin et al [53] who carried out training-testing on rainfall and temperature data from Lombok International Airport station. Furthermore, Syaharuddin et al [44,54] also tested several parameters of the backpropagation architecture with three hidden layers.…”
Section: Research Proceduressupporting
confidence: 87%
“…Thus, from these two architectural models, it was found that the three hidden layers (100-50-10-1) have predictive results derived from the actual data and can be used for forecasting calculations in future periods; or the MSE and RMSE value of three hidden layers is smaller than that of two hidden layers. This finding is supported by the research of Syaharuddin et al [32] who argued that the determination of the best number of neurons on backpropagation using three layers with an architecture of 36-73-37-19-1 showed the highest level of accuracy at the time of precipitation data, obtaining an MSE of 0.0291 and an accuracy rate of 99.94% for data training and 99.99% for data testing.…”
Section: Training Testing and Data Prediction Phasesupporting
confidence: 58%
“…A BP neural network with three hidden layers is chosen for data training. The number of neurons in the three hidden layers is set as 17, 10, and 6 (the number of neurons in the hidden layers can be determined based on empirical formulas [52,53]). The neural network's input layer includes the eight design parameters of the actuator.…”
Section: Network Prediction Model and Its Application For Rigidly-con...mentioning
confidence: 99%